Factors Affecting Variation Orders in the Construction Project of Antasari Place Jakarta Apartment - Antonius, Kevien Benaya; Sucita, I Ketut (Universitas Negeri Padang, 2023)
A Variation Order is a modification of the contract content that has been agreed at the pre-implementation stage. Variation Order often occurs in a construction project and has the possibility to have a positive or negative impact on the project implementation time. In the implementation of the Antasari Place Jakarta apartment construction project, there are 22 site instructions as an order for Variation Order work. In identifying factors affecting the Variation Order in this study, a questionnaire that has been validated by experts was used. This study identified 21 factors from the aspects of construction, administration, parties involved, and others that affect the Variation Order on the Antasari Place Jakarta Apartment construction project, with the most dominant factor affecting the Variation Order is the addition of work scope. Ranking of the most dominant factors using the Relative Importance Index (RII) method and ranked three factors with the highest RII values, namely due to the addition of the scope of work with an RII score of 0.900, design changes from planning with an RII score of 0.680, and changes in the scope of work at the construction implementation stage with an RII score of 0.620. The Variation Order work in the Antasari Place Jakarta Apartment construction project has no impact on the final completion time of the project contract because the project implementation has not entered the critical trajectory of the implementation time and is carried out during slack time.